INNOVATIVE METHODS OF COST MANAGEMENT IN MODERN BUSINESS CONDITIONS - LOPATOVSKA, Oksana; OSTROVSKAYA, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2023)
An important function of the economic mechanism of any enterprise is the management of its costs. This is due to the fact that any activity, and especially production, requires significant expenditure of resources. The functioning of the enterprise and its competitiveness directly depend on the level of operating costs. In a market economy, costs are the basis for choosing the best of alternative options for the development of an enterprise and making balanced management decisions, a guideline for setting the price of products and a prerequisite for increasing the enterprise’s capital. The effectiveness of adaptive actions of manufacturing enterprises to changes in the economic situation in the country or the immediate industry and their ability to work stably depend to a large extent on the provision of information management systems about the state and prospects of business, existing and potential problems, and alternative directions of development. On the one hand, costs are a necessary condition for the full functioning of any enterprise, and on the other hand, they directly affect the financial result of its activity, as the foundation of the enterprise’s development, and characterize the efficiency of the use of available resources. They are diverse, constantly changing under the influence of both the internal and external environment, and have different dynamics in different periods of time. All this prompts active current and strategic cost management, the purpose of which is to realize the competitive advantages of the manufacturing enterprise and secure it in positions of stable development. Such orientation should stimulate the introduction of the latest cost management technologies, which, in turn, will contribute to successful integration into the global and European economic space. At the same time, the effective functioning of domestic management will be ensured by innovative tools that have been tested at enterprises of the developed world economy and require adaptation to the real conditions of functioning of domestic enterprises. Therefore, the problem of cost management is relevant in the economy of European and world-class enterprises and is too relevant for domestic production to ensure stable profitable activity and competitive advantages in the market of goods and services.